WOMEN’S LEADERSHIP IN MADURA: Analysis of Women’s Leadership in Student Organizations at Higher Education in Madura - Azizah, Siti; Itaanis Tianah (Islamuna: Jurnal Studi Islam, 2024)
ABSTRACT In modern society, women have more opportunities to participate in public spheres. However, in Madura, Indonesia, social expectations rooted in patriarchal norms still limit their leadership potential, especially in student organizations. In fact, of the 257 student organizations in 8 universities, only 18% are led by women. This study explores how Madurese students perceive female leadership, how female students view their own leadership abilities, and how these perceptions, shaped by social beliefs and gender stereotypes, influence their involvement in these organizations. Based on Emile Durkheim’s concept of social facts, this study examines how family values, religious interpretations of female leadership roles, and campus and community environments shape these perceptions. Using a qualitative research methodology with a sociological perspective, this study highlights the factors that influence female leadership aspirations in higher education in Madura. The findings of this study highlight the role of a supportive environment in countering negative social constructs and empowering women to pursue leadership roles in student organizations. ABSTRAK Meskipun era modern membuka peluang yang lebih luas bagi perempuan untuk berkiprah di ranah publik, di Madura, ekspektasi sosial yang berakar pada norma patriarki masih membatasi potensi kepemimpinan mereka, khususnya dalam organisasi kemahasiswaan. Faktanya, dari 257 organisasi mahasiswa di 8 perguruan tinggi, hanya 18 % yang dipimpin oleh perempuan. Penelitian ini mengeksplorasi bagaimana persepsi mahasiswa Madura tentang kepemimpinan perempuan, bagaimana mahasiswi memandang kemampuan kepemimpinan mereka serta bagaimana persepsi ini, yang dibentuk oleh keyakinan sosial dan stereotip gender, memengaruhi keterlibatan mereka dalam organisasi tersebut. Berdasarkan konsep fakta sosial Emile Durkheim, penelitian ini meneliti bagaimana nilai-nilai keluarga, interpretasi agama tentang peran kepemimpinan perempuan, serta lingkungan kampus dan komunitas membentuk persepsi ini. Dengan menggunakan metodologi penelitian kualitatif perspektif sosiologis, penelitian ini menyoroti faktor-faktor yang memengaruhi aspirasi kepemimpinan perempuan dalam pendidikan tinggi di Madura. Temuan penelitian ini menyoroti peran lingkungan yang mendukung dalam melawan konstruksi sosial negative dan memberdayakan perempuan untuk mengejar peran kepemimpinan dalam organisasi kemahasiswaan.